2009
DOI: 10.1111/j.1440-1746.2009.05786.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of adalimumab for the management of Inflammatory Bowel Disease in the Clinical Setting

Abstract: In CD, adalimumab is as, if not more, effective in the clinical setting than in the trials, and is effective in patients with an attenuated response to infliximab. Its efficacy is not as good in UC, but this requires further clarification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 18 publications
4
37
0
Order By: Relevance
“…However, 77% (14/18) of the cases may achieve remission in week 48. These results also suggest that in patients with partial response to standard treatment with ADA, weekly injections could be an effective option, as shown by other studies (11,12). Other authors have observed acceptable remission rates even in patients with primary failure to IFX such as in the GAIN study (13)(14)(15).…”
Section: Discussionsupporting
confidence: 67%
“…However, 77% (14/18) of the cases may achieve remission in week 48. These results also suggest that in patients with partial response to standard treatment with ADA, weekly injections could be an effective option, as shown by other studies (11,12). Other authors have observed acceptable remission rates even in patients with primary failure to IFX such as in the GAIN study (13)(14)(15).…”
Section: Discussionsupporting
confidence: 67%
“…The effect of vitamin D 3 on the CDAI scores was remarkable with all but one patient having a decrease in CDAI score and 78% of the patients had a drop of 70 points or more, which is considered a treatment response in the clinic. 20, 21 The vitamin D 3 effect was also reflected in the improved IBDQ scores, which is a second validated assessment tool used to monitor therapeutic efficacy in clinical trials of IBD. 22, 23 The IBDQ questionnaire consists of 32 questions scored in four domains: bowel symptoms, emotional health, systemic systems, and social function.…”
Section: Discussionmentioning
confidence: 99%
“…Adalimumab, a fully human IgG1 monoclonal antibody to TNF-, was found to be effective in patients with CD refractory to conventional therapy and in patients with an attenuated response to infliximab [211,227,228]. Recent study showed that adalimumab could induce and maintain clinical remission in patients with moderate-to-severe UC as well, who did not have a satisfactory response to steroids or immunosuppressive agents [229].…”
Section: Inhibition Of Pro-inflammatory Cytokines 3211 Inhibitorsmentioning
confidence: 99%